Family medicine practices across the globe: Nepal focus - Dangal, Binod (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Family medicine attributes accessible, comprehensive and quality health care and represents combination of high values in national health care system. Family medicine practice is different around the globe in primary care upliftment. Nepal has exceptionally established General Practice (also known as family medicine) program in 1982 to serve for rural communities treating medical to specialty based emergency surgical problems providing high quality care with cost effective strategy. Recognition of family medicine to improve primary care is a major challenge.